Dr. Quinn medicine woman. The complete season five [videorecording (DVD)]. - Seymour, Jane, 1951-; Lando, Joe, 1961-; Allen, Chad, 1974-; Toovey, Shawn (A & E Home Video, 2011)
With an adopted family of three orphaned children, a new baby, and mountaineer Byron Sully by her side, Dr. Quinn and crew lead the way into a changing America in the fifth season of this landmark series. Features all 26 episodes with everything from a train robbery to a mysterious disease killing everyone in Mike's clinic, to a dangerous hostage situation. Bonus features: commentary by Shawn Toovey and Chad Allen on 'Legend, ' and cast biographies. This title has been repackaged.